Some Suggestions for Controlling Benghal Dayflower in Field Nurseries - Robert H. Stamps (EDIS)
ENH-1085, a 9-page illustrated fact-sheet by Robert Stamps, describes this increasingly problematic weed — also known as jio, tropical spiderwort, hairy wandering jew, and Indian dayflower — in field nurseries, its identification, control, factors effecting pre- and post-emergence herbicides, tables of recommended herbicides, and references. Published by UF Department of Environmental Horticulture, January 2008.